Acceptability and feasibility of the use of 400 μg of sublingual misoprostol after mifepristone for medical abortion up to 63 days since the last menstrual period: Evidence from Uzbekistan. (April 2013) - Raghavan, Sheila; Tsereteli, Tamar; Kamilov, Asamidin; Kurbanbekova, Dilfuza; Yusupov, Dilmurod; Kasimova, Feruza; Jymagylova, Dilbar; Winikoff, Beverly
ABSTRACT Objective To examine the efficacy, acceptability and feasibility of early medical abortion, with the option of home administration of misoprostol, in Uzbekistan. Methods A total of 450 women were enrolled at national, municipal and private facilities in Tashkent, Uzbekistan. Women who presented for termination of pregnancy with gestations up to 63 days were recruited to participate in the study. All eligible pregnant women who consented to participate swallowed a 200 mg mifepristone pill in the clinic and were given the option of taking 400 μg misoprostol sublingually either at the clinic or at home 24–48 hours after mifepristone administration. Abortion status was determined two weeks later. Results Almost all women (99.5%) chose home administration of misoprostol. The sublingual route of misoprostol administration was acceptable or very acceptable to 89% of participants. Ninety-five percent of women had complete abortions after mifepristone and misoprostol. Almost all participants preferred a medical abortion to surgery for a future procedure (95%). Conclusions Mifepristone medical abortion with home administration of misoprostol is an acceptable and feasible option for women in Uzbekistan. The method worked well at all three facility types.